2017
DOI: 10.1037/xlm0000335
|View full text |Cite
|
Sign up to set email alerts
|

Dependent measure and time constraints modulate the competition between conflicting feature-based and rule-based generalization processes.

Abstract: In our study, we tested the hypothesis that feature-based and rule-based generalization involve different types of processes that may affect each other producing different results depending on time constraints and on how generalization is measured. For this purpose, participants in our experiments learned cue-outcome relationships that followed the opposites rule: Single cues that signaled the same outcome (e.g., A-1/B-1) predicted the opposite outcome when presented in compound (e.g., AB-2). Some cues were on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 50 publications
(78 reference statements)
1
20
0
Order By: Relevance
“…One example is the Perruchet (1985, 2015) effect, where within the same experiment and indeed the same trial, diverging response patterns can be obtained in two behavioral systems (for example eye blink conditioning and causal rating; for details see below). Cobos et al (2016) observed diverging “associative” and “non-associative” response generalization in cued response times and verbal ratings, respectively and Morís et al (2014, Exp 4) found that non-associative knowledge, given by instruction, affects verbal judgements but not responses in a recognition priming-based test. But a related and in many ways more difficult question is how associative predictions might generate explicit judgements.…”
Section: How Might Non-associative Knowledge Influence An Associativementioning
confidence: 93%
See 2 more Smart Citations
“…One example is the Perruchet (1985, 2015) effect, where within the same experiment and indeed the same trial, diverging response patterns can be obtained in two behavioral systems (for example eye blink conditioning and causal rating; for details see below). Cobos et al (2016) observed diverging “associative” and “non-associative” response generalization in cued response times and verbal ratings, respectively and Morís et al (2014, Exp 4) found that non-associative knowledge, given by instruction, affects verbal judgements but not responses in a recognition priming-based test. But a related and in many ways more difficult question is how associative predictions might generate explicit judgements.…”
Section: How Might Non-associative Knowledge Influence An Associativementioning
confidence: 93%
“…Associative networks generally anticipate this difference because the summation of associations formed to the single stimuli in negative patterning (C+ and D+ trials) provides a particularly strong and incorrect prediction for the compound (CD-). However, from an abstract relational perspective, positive and negative patterning possess the same complexity; they are perfect examples for a simple rule that the outcome of the compound is always the opposite of the outcome of the single cues (Shanks and Darby, 1998; Lachnit et al, 2001, 2002; Harris and Livesey, 2008; Cobos et al, 2016). Capitalizing on this simple relational property, Shanks and Darby also trained participants on a series of single cues (I+/J+/M-/N-) and compounds (KL-/OP+), and later tested how participants would predict the consequences of these cues in novel combinations (e.g., IJ?…”
Section: Issues Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…But requesting a verbal judgment may be less than ideal if the objective is to evaluate the intervention of associative processes. Usually, participants are provided with sufficient time to give their ratings and thus, goal-directed propositional processes can override responses from any competing associative processes [7, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that both accounts are based on the operation of associative learning and associative retrieval mechanisms. Associative mechanisms are thought to be fast acting, automatic, and require little cognitive resources to operate (e.g., Cobos, Gutiérrez-Cobo, Morís, & Luque, 2017;Morís, Cobos, Luque, & López, 2014;Shanks, 2007;Wagner, 1981). Because of this, they are prototypic of the low-level processes proposed by two system theories, as opposed to high-level inference processes (see Darlow & Sloman, 2010, for a review).…”
mentioning
confidence: 99%